2017
DOI: 10.3389/fgene.2017.00120
|View full text |Cite
|
Sign up to set email alerts
|

The Bunocephalus coracoideus Species Complex (Siluriformes, Aspredinidae). Signs of a Speciation Process through Chromosomal, Genetic and Ecological Diversity

Abstract: Bunocephalus is the most species-rich Aspredinidae genus, corresponding to a monophyletic clade with 13 valid species. However, many species have their classification put in question. Here, we analyzed individuals from four Amazonian populations of Bunocephalus coracoideus by cytogenetic and molecular procedures. The geographic distribution, genetic distances and karyotype data indicate that each population represents an Evolutionary Significant Unit (ESU). Cytogenetic markers showed distinct 2n and karyotype … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
1
15
0
Order By: Relevance
“…Most of the species of Farlowella present reduced vagility and inhabit specific portions of the river, which may lead to the formation of small, isolated populations, in which independent processes of genetic differentiation may result in speciation. This type of process has been observed in both sympatric and allopatric populations of Bunocephalus coracoideus, for example, which presents innumerable cytotypes, resulting from chromosomal rearrangements fixed in small populations (Ferreira et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Most of the species of Farlowella present reduced vagility and inhabit specific portions of the river, which may lead to the formation of small, isolated populations, in which independent processes of genetic differentiation may result in speciation. This type of process has been observed in both sympatric and allopatric populations of Bunocephalus coracoideus, for example, which presents innumerable cytotypes, resulting from chromosomal rearrangements fixed in small populations (Ferreira et al, 2017).…”
Section: Discussionmentioning
confidence: 93%
“…Chromosomal mapping of rDNA clusters has repeatedly helped to unveil diverse evolutionary issues (e.g., [82,83]). Particularly in fishes, it provided valuable clues about the incidence of cryptic, morphologically indistinguishable sibling species [5,6,8,10,84], polyploidization and interspecific hybridization events [85,86], a geographical gradient of genomic and morphological change [87], patterns of sex chromosome differentiation [80,[88][89][90], and the correlation of genome dynamics in response to environmental cues [91,92]. Among the Nannostomus species investigated here, chromosomal mapping revealed somewhat uniform patterns of distribution for both rDNA classes, with one to few sites of accumulation, as found in most fishes [93,94], as well as in some other lebiasinids [21,22] investigated to date.…”
Section: Discussionmentioning
confidence: 99%
“…The Neotropical region harbors the richest freshwater ichthyofauna in the world, with approximately 5200 species belonging to 17 orders, thus representing about 40% of the freshwater biodiversity worldwide [1][2][3]. Moreover, the amount of cryptic and until now morphologically undistinguishable species suggests much higher species diversity (e.g., [4][5][6][7][8][9]). Fueled by these discoveries, the knowledge about the karyotype differentiation in Neotropical fishes has been rapidly growing (especially during the last few decades) and several important models for studying both sympatric and allopatric speciation, species complexes, and sex chromosome evolution have emerged [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This genetic tool can be used for a variety of purposes, from forensic analyses and studies for species conservation (Ardura et al 2010;Carvalho et al 2015;Shen et al 2016;Barman et al 2018) to taxonomic studies (de Borba et al 2019). Several authors have also shown the efficiency of DNA barcoding for fish species identification (Benzaquem et al 2015;Ferreira et al 2017;Barendse et al 2019).…”
Section: Introductionmentioning
confidence: 99%